Alternate hosts of spongospora subterranea f. sp. subterranea identification in colombia by bioassay / identificación de hospederos alternos de spongospora subterranea f. sp. subterranea en colombia por bioensayos (2013)
Potato powdery scab, caused by Spongosporasubterranea f. sp. subterranea, is a disease that limits worldwide potato crop production. Incidence of the disease has been increasing in Colombia, thereby affecting tubers production, so far effective control methods have yet to be developed. The aim of this research was to establish the host range plants for Spongospora subterranea f. sp. subterranea by artificial inoculations. Thus, 33 species were inoculated with 1×106 sporosori.mL-1 solution for 12 days. The plants were then planted in field, evaluations were performed at 15, 30, 60, 90 and 120 days after inoculation, 10 plants of each species were selected for every evaluation, the rootswere stained and the pathogenic structures were identified bymicroscopy. Morphological examination enabled the identification of trap plants species, which presented zoosporangia only; Type I hosts, which present sporosori only; and Type II hosts, which presented both sporosori and zoosporangia. Some of these hosts belonged to the Alliaceae, Apiaceae, Brassicaceae, Poaceae, Polygonaceae and Solanaceae families, thus extending the speciesrange that can be reported as hosts of Spongospora subterranea f. sp. subterranea in Colombia. / El agente causal de la sarna polvosa de la papa,Spongospora subterranea f. sp. subterranea es una de lasenfermedades más limitantes de la producción del cultivo anivel mundial. En Colombia, viene incrementando su incidencia al punto de disminuir la producción, sin llegar a encontrar métodos de control efectivos. En este estudio, se buscó establecer un rango de hospederos del patógeno a partir de inoculaciones por bioensayos. Así, plantas de 33 especies se inocularon en solución a una concentración de 1x106 quistosoros mL-1 durante 12 días; posteriormente, las plantas fueron sembradas en campo, realizando evaluaciones a los 15, 30, 60, 90 y 120 días después de inoculadas. En cada evaluación se seleccionaron diez plantasde cada especie, con el fin de hacer tinción de raíces e identificar al microscopio estructuras asociadas al patógeno. A partir de la identificación morfológica fue posible clasificar las especies como plantas trampa quienes sólo presentaron zoosporangios, hospedero Tipo I con presencia sólo de quistosoros y hospederos Tipo II quienes presentaron estructuras de zoosporangios y quistosoros. Algunos de éstos hospederos pertenecen a las familias Alliaceae, Apiaceae, Brassicaceae, Poaceae, Polygonaceae, Solanaceae, ampliándose así el rango de especies que pueden serreportadas como hospederas de Spongospora subterranea f. sp. subterranea en Colombia.